A PARTICIPATIO DE TOMÁS DE AQUINO NA PROPOSTA DOUTRINAL DO NOVO CATECISMO DA IGREJA CATÓLICA - CHADAREVIAN , ELIE (2016)
The proposal of the new Catechism of the Catholic Church is, from an abstract point of view, transformative and even revolutionary, if we think, for example, on the extraordinary importance that, for the first time, is given to the lay faithful, as full members of the Church, and in the daily life, due to a new conception of the reach of Baptism, whose physical and metaphysical dimensions (natural and supernatural), drive their persons to act no longer as simple "members card-carrying", but as son/daughter of God, effectively imbued of divinity, which is clearly noticeable by the perspective of the concept of participation - the participatio - developed by Thomas Aquinas, which permeates all new Catechism of the Catholic Church in its four major parts (the doctrine of faith # 26 - # 1065, the Liturgy # 1066 - # 1690, Moral # 1691 - # 2557 and lives of Prayer # 2558 - # 2865), as is shown in this study, where 234 instances of participation and its related (to participate, participant etc.) were recorded, of which 171 (73%) are in the deepest sense proposed by Thomas. However, in this quarter century, since it was promulgated the CIC, it's not noted in the pastoral and in the Catholic education the corresponding significant expected changes.